Coping with 21st Century Opportunities and Challenges: English Teacher Professional Competence Development - Nur Azizah (Jurnal Bahasa dan Sastra, 2018)
Abstract: The development of information and communication technology in the 21st century requires teachers of English as a foreign language (EFL) to be more professional to scaffold students to reach the global requirements. To be professional, teachers can participate in several modes based on certain demands as required by experts, world organization, and the Indonesian Ministery of Education. However, there are problematic aspects which should be considered, such as conflicts in the workplace, lacks of motivation, personal matters, costs spent, limited chances, and specifications of needs. Due to the problems which may be faced by individual teachers, informal modes can be the ways out fortheir professional development. Teachers can do independent self-development by using ICT as one of the educational devices in this era. This paper highlights teacher professional competence development in relation to the use of ICT as either opportunities or challenges in enhancing the quality of EFL teachers.Keywords: EFL teachers, ICT in 21st century, professional developmentAbstrak: Perkembangan teknologi informasi dan komunikasi (TIK) di abad ke-21 ini menun- tut guru bahasa Inggris sebagai bahasa asing (BIBA) menjadi lebih profesional dalam rangka membantu siswa mereka memenuhi berbagai tuntutan dunia global. Untuk menjadi profesional, guru dapat melakukan berbagai cara sesuai kebutuhan tertentu, seperti yang telah disyaratkan oleh para ahli, organisasi dunia, dan Kementerian Pendidikan Republik Indonesia secara for- mal. Meskipun demikian, ada beberapa aspek permasalahan yang seharusnya dipertimbangkan, seperti konflik ditempat kerja, kurangnya motivasi, permasalahan pribadi, biaya yang dikel- uarkan, keterbatasan kesempatan, dan spesifikasi kebutuhan. Untuk menghadapi permasala- han yang mungkin terjadi secara individu, guru dapat menggunakan cara-cara informal se- bagai jalan keluar dalam melaksanakan pengembangan kompetensi profesionalnya. Guru dapat mengembangkan diri sendiri secara mandiri dengan memanfaatkan ICT sebagai salah satu alat pendidikan di era ini. Makalah ini menyoroti pengembangan kompetensi profesional guru ter- kait penggunaan ICT baik sebagai suatu kesempatan maupun tantangan dalam meningkatkan kualitas guru bahasa Inggris.Kata-kata kunci: Guru EFL, TIK di abad 21, pengembangan keprofessionalan